High BMP7 Expression May Worsen Airway Disease in COPD by Altering Epithelial Cell Behavior - Dong W; Xie M; Ming C; Li H; Xu X; Cui L; Wang W; Li Y (International Journal of COPD)
Wenyan Dong,1,* Mengshuang Xie,2,* Chunjie Ming,3 Haijun Li,2 Xia Xu,2 Liwei Cui,4 Wei Wang,5 Yi Li6 1Department of General Practice, The Second Hospital, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People’s Republic of China; 2Department of Geriatric Medicine, Laboratory of Gerontology and Anti-aging Research, Qilu Hospital, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People’s Republic of China; 3National Key Laboratory for Innovation and Transformation of Luobing Theory, The Key Laboratory of Cardiovascular Remodeling and Function Research, Chinese Ministry of Education, Chinese National Health Commission and Chinese Academy of Medical Sciences, Department of Cardiology, Qilu Hospital, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People’s Republic of China; 4Department of Pulmonary and Critical Care Medicine, Qilu Hospital, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People’s Republic of China; 5Medical Integration and Practice Center, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People’s Republic of China; 6Department of Obstetrics and Gynecology, Qilu Hospital, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Wang; Yi Li, Email styw28@163.com; 202062009073@email.sdu.edu.cnPurpose: Airway disease is the main pathological basis of chronic obstructive pulmonary disease (COPD), but the underlying mechanisms are unknown. Bone morphogenetic protein-7 (BMP7) is a multi-functional growth factor that belongs to the transforming growth factor superfamily, which affects the regulation of proliferation, differentiation, and apoptosis. Previous research has shown that BMP7 is highly expressed in the airway epithelia of patients with COPD, but its role in airway disease has not been fully elucidated.Methods: A lung tissue cohort and a sputum cohort were included in the study. BMP7 expression in the airway epithelium and the BMP7 level in sputum supernatants were detected. Human primary bronchial epithelial cells (HPBECs) were isolated by bronchoscopy from healthy individuals. The functional consequences of adding recombinant human BMP7 or BMP7 overexpression to HPBECs were explored.Results: BMP7 expression in bronchial epithelial cells of patients with COPD was significantly higher than that in smoking and nonsmoking controls. The expression of BMP7 in the bronchial epithelia of patients with COPD was negatively correlated with the airway counts measured by quantitative computed tomography, positively correlated with airway wall thickness, and negatively correlated with FEV1. The BMP7 level in the induced sputum of patients with COPD was higher than that in controls, and was related to the levels of interleukin-6 (IL-6), IL-8, and IL-1β. The addition of rhBMP7 (100 ng/mL) inhibited the proliferation of HPBECs and promoted squamous metaplasia and inhibit ciliated cell differentiation in human bronchial epithelial cells. BMP7 overexpression promotes apoptosis in human bronchial epithelial cells, through regulating MKK7/JNK2 signaling pathway and activating the caspase-3 pathway.Conclusion: High expression of BMP7 in the bronchial epithelia may play a crucial role in airway disease of COPD through inhibiting proliferation and promoting abnormal differentiation and excessive apoptosis of human bronchial epithelial cells.Keywords: COPD, BMP7, airway disease, remodeling, apoptosis